Luminescent Yttrium–Aluminum Garnet Ceramics Obtained by Conventional Sintering on Air; Nanotechnologies in Russia; Vol. 14, iss. 3-4 - Paygin V. D. Vladimir Denisovich; Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Vaganov V. A. Vitalii Andreevich; Alishin T. R. Timofey Ruslanovich; Kalashnikov M. P. Mark Petrovich; Ilela A. E. Alfa Edison (2019, 2019)
Title screen